Nerve - Piper, Martha C.; Samarasekera, Indira Vasanti, 1952- (Tantor Media, Inc., 2021)
Candid and insightful perspectives on the dilemmas and opportunities women confront as they take on leadership positions Martha Piper and Indira Samarasekera had vastly different career paths on their way to becoming the first (and so far only) female presidents of two of Canada's largest and most respected research universities and directors of some of the nation's largest market cap companies, but what they had in common was their gender, their willingness to take risks when leadership opportunities presented themselves, and a work ethic second to none. It was not always easy, pretty, or fair, but it was always the result of choosing to answer the call to lead. A call that in the authors' view, too many women still turn away from. In Nerve: Lessons on Leadership from Two Women Who Went First, Piper and Samarasekera share their personal and professional stories, offering guidance for women leaders of every age and at every stage of their career. Nerve is a must-listen for any woman who is leading today, considering leading, or thinking about life after leading.